“Luka Tak Terlihat”: Studi Kasus Tentang Labelling dan Pembentukan Konsep Diri Siswa dalam Bingkai Pendidikan Karakter Kristen di Sekolah - Helmi Yultrisani Rolantika Muris; Jonathan Leobisa (Journal of Student Research, 2026)
Schools are formal educational institutions that play a crucial role in transferring knowledge and shaping students' cognitive, psychomotor, and character development systematically and responsibly. While the "school of life" is often defined as a non-formal learning space, formal schools retain a strategic position because they provide a clear ontological, epistemological, and axiological framework, including in the formation of students' character and self-concept. However, the reality on the ground shows that labeling practices are still prevalent in the school environment, both by teachers and fellow students, which negatively impact students' psychological, emotional, social, and self-concept. Negative labels such as stupid, lazy, naughty, or physical and social labels have been shown to cause "invisible wounds" that affect students' self-esteem and functioning in the long term. This study uses qualitative methods through a literature review to examine the phenomenon of labeling and its impact on the formation of students' self-concept within the framework of Christian Character Education. The results of the study indicate that Christian Character Education, which is based on the values ​​of love, acceptance, and respect for human dignity as God's creation, has a strategic role in restoring the self-concept of students affected by labeling. Christian character education not only instills moral and ethical values, but also builds students' inner and spiritual resilience so that they are able to interpret themselves positively, regardless of the negative labels they receive.